Pyridalthiadiazole acceptor-functionalized triarylboranes with multi-responsive optoelectronic characteristics. Issue 8 (7th June 2017) - Yin, Xiaodong; Liu, Kanglei; Ren, Yi; Lalancette, Roger A.; Loo, Yueh-Lin; Jäkle, Frieder
Abstract : The functionalization of triarylboranes with pyridalthiadiazole (PT) acceptor moieties gives Ar2 B–π–PT dyads and PT–π–B(Ar)–π–PT triads with low-lying PT-centered LUMO orbitals. Addition of a fluoride source results in competing anion binding to boron and PT reduction, depending on the steric and electronic structure of the B-aryl group. Abstract : A new class of Ar2 B–π–A dyads and A–π–B(Ar)–π–A triads that feature strong organic acceptor moieties (A = pyridalthiadiazole, PT) attached to a central triarylborane were synthesized via Stille cross-coupling of ArB(Th–SnMe3 )2 (Th = thiophenediyl, Ar = 2, 4, 6-tri- tert -butylphenyl (Mes*) or 2, 4, 6-tris(trifluoromethylphenyl) ( F Mes)) with one or two equivalents of dibromopyridalthiadiazole. Single-crystal X-ray crystallography data for the triad Mes*B(Th–PT–Br)2 indicate a highly coplanar conformation, which is ideal for extended π-conjugation and favors intermolecular π-stacking. Despite the presence of Br substituents, these compounds exhibit strong photoluminescence in THF solution with quantum yields reaching up to 52%. Further extension of conjugation by coupling with 2-hexylthiophene leads to additional bathochromic shifts to give a highly soluble and strongly red-emissive material. All these compounds undergo facile reduction, first of the PT substituents and then at more negative potentials for the borane moiety. Upon chemical reduction with in THF, an intramolecular charge transfer (ICT) pathway from the reduced PT moieties to boron is enabled and this results in a change of the color to blue. Theoretical calculations reveal that, due to the electron-withdrawing effect of the PT moieties, not only the PT-centered LUMOs themselves but also the LUMO+1 or LUMO+2, which show contributions from the p orbital of boron, experience a significant decrease in energy; they are much lower in energy than those of typical conjugated triarylboranes. The relatively low energy of both the PT-centered LUMOs and boron-centered LUMO+1 or LUMO+2 opens up multiple pathways for reaction with highly nucleophilic fluoride anions. Evidence for very strong F − binding to boron is obtained in the case of the more sterically accessible F Mes derivatives. Fluoride anion binding leads to an electron-rich borate moiety and as such generates an ICT pathway to the electron-deficient PT moieties; the direction of this ICT is opposite to that observed upon chemical reduction. For the Mes* derivatives, F − binding is hindered, resulting in competing reduction of the PT acceptors. Finally, the electron acceptor character of the hexylthiophene derivative is exploited in electron-only diodes that show an average electron mobility of 6.4 ± 1.6 × 10 −5 cm 2 V −1 s −1 .